Differences in Components at Delayed-Type Hypersensitivity Reaction Sites in Mice Immunized with Either a Protective or a Nonprotective Immunogen of Cryptococcus neoformans - Nichols, Kasie L. (American Society for Microbiology, 2002)
Cell-mediated immunity is the major protective mechanism against Cryptococcus neoformans. Delayed swelling reactions, i.e., delayed-type hypersensitivity (DTH), in response to an intradermal injection of specific antigen are used as a means of detecting a cell-mediated immune (CMI) response to the antigen. We have found previously that the presence of an anticryptococcal DTH response in mice is not always indicative of protection against a cryptococcal infection. Using one immunogen that induces a protective anticryptococcal CMI response and one that induces a nonprotective response, we have shown that mice immunized with the protective immunogen undergo a classical DTH response characterized by mononuclear cell and neutrophil infiltrates and the presence of gamma interferon and NO. In contrast, immunization with the nonprotective immunogen results in an influx of primarily neutrophils and production of tumor necrosis factor alpha (TNF-α) at the DTH reaction site. Even when the anticryptococcal DTH response was augmented by blocking the down-regulator, CTLA-4 (CD152), on T cells in the mice given the nonprotective immunogen, the main leukocyte population infiltrating the DTH reaction site is the neutrophil. Although TNF-α is increased at the DTH reaction site in mice immunized with the nonprotective immunogen, it is unlikely that TNF-α activates the neutrophils, because the density of TNF receptors on the neutrophils is reduced below control levels. Uncoupling of DTH reactivity and protection has been demonstrated in other infectious-disease models; however, the mechanisms differ from our model. These findings stress the importance of defining the cascade of events occurring in response to various immunogens and establishing the relationships between protection and DTH reactions.